COMPORTAMENTO TÉRMICO, MECÂNICO E MORFOLÓGICO DO COMPÓ-SITO DE POLIPROPILENO E PÓ DE MADEIRA ACETILADA POR ANIDRIDO ACÉTICO E ÁCIDO ACÉTICO - Stasievski, Gisele (2016)
The composites with wood load have been gaining space among the materials of this class because their good mechanical properties, dimensional stability, low cost, and contribute for the environmental factor. For a good adhesion of wood particles in polymeric matrix, a compatibility process are required, because wood have polar characteristic meanwhile polymers have a-polar groups. The process used in this study is a chemical treatment by acetylation, where the purpose is to reduce the polarity of wood and ensure strong adhesion between components. A mixture of equal proportions of acetic acid and acetic anhydride catalyzed by sul-furic acid are the reagents of the pine wood acetylation. The treated wood was processed with polypropylene and infrared spectroscopy was used to analyze composite effective chemical modification. The thermal and mechanical proper-ties were compared to virgin polymer and adhesion between fiber-matrix was ver-ified by microscopic analysis.